2003
DOI: 10.1051/0004-6361:20021537
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of flares on late type dMe stars

Abstract: Abstract.We investigate the spectral signatures of stellar flares in the wavelength range 3600 Å to 4500 Å and in broad band photometry. We study the phenomenology of the spectral signatures and we found that flares are best described by two main phases; an impulsive phase and a gradual phase, for which the physical properties are different. Important spectral differences between flares lead us to distinguish four main classes: (i) solar-like chromospheric or two-ribbon flares, (ii) white-light flares, (iii) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
21
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 26 publications
7
21
1
Order By: Relevance
“…This behaviour is compatible with what is normally observed for the Ca ii H and K lines, which decay more gradually than Balmer and Helium lines (e.g. Houdebine et al 1993), consistent with an interpretation of a faster evolution of high-temperature lines in the chromosphere (Houdebine 2003). The optical spectral data allowed us to trace the chromospheric reaction to the flare (with one He ii transition line covered).…”
Section: Discussionsupporting
confidence: 89%
“…This behaviour is compatible with what is normally observed for the Ca ii H and K lines, which decay more gradually than Balmer and Helium lines (e.g. Houdebine et al 1993), consistent with an interpretation of a faster evolution of high-temperature lines in the chromosphere (Houdebine 2003). The optical spectral data allowed us to trace the chromospheric reaction to the flare (with one He ii transition line covered).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the gas that is heated and evaporated into the newly formed loop after magnetic reconnection (Cargill & Priest 1983;Forbes & Malherbe 1986) cools and reaches the formation temperature of the Balmer series before the one of the Ca ii H & K lines. Houdebine (2003) found that the rise and decay times in the Ca ii K and Hγ lines obey good relationships, which implies that there is a well-defined underlying mechanism responsible for the flux time profiles in these lines. Our results show that the duration of flares tends to be larger when the EWRQ max of the Balmer lines is greater.…”
Section: Equivalent Widths Relative To the Quiescent Statementioning
confidence: 84%
“…Within a single flare, multiple peaks and changes in the decay rate are possible. Some researchers have identified as flares events in which the stellar flux rises and fades more gradually (Houdebine 2003;Tovmassian et al 2003).…”
Section: A Brief Discussion Of Stellar Variabilitymentioning
confidence: 99%